Clinical characteristics, quality of life and risk factors for severity in palmoplantar pustulosis: a cross‐sectional, multicentre study of 263 patients. (25th August 2021) - Sarıkaya Solak, S.; Kara Polat, A.; Kilic, S.; Oguz Topal, İ.; Saricaoglu, H.; Karadag, A. S.; Canpolat, F.; Kartal, S. P.; Deveci, B. N.; Kacar, N.; Polat Ekinci, A.; Guner, R.; et al.
Summary: Background: Palmoplantar pustulosis (PPP) is a rare, chronic, inflammatory skin disease characterized by sterile pustules on palmar or plantar areas. Data on PPP are scarce. Aim: To investigate the clinical characteristics and risk factors for disease severity in a large cohort of Turkish patients with PPP. Methods: We conducted a cross‐sectional, multicentre study of patients with PPP recruited from 21 tertiary centres across Turkey. Results: In total, 263 patients (165 women, 98 men) were evaluated. Most patients (75.6%) were former or current smokers. The mean Palmoplantar Pustulosis Area and Severity Index (PPPASI) was 8.70 ± 8.06 and the mean Dermatology Life Quality Index (DLQI) score was 6.87 ± 6.08, and these scores were significantly correlated ( r  = 0.52, P  < 0.001). Regression analysis showed that current smoking was significantly associated with increased PPPASI ( P  = 0.03). Coexisting psoriasis vulgaris (PsV) was reported by 70 (26.6%) patients. Male sex prevalence, PPP onset incidence, disease duration, DLQI, and prevalence of nail involvement and psoriatic arthritis (PsA) were significantly increased among patients with PPP with PsV. Of the 263 patients, 18 (6.8%) had paradoxical PPP induced by biologic therapy, and these patients had significantly increased mean DLQI and prevalence of PsA ( r  = 0.03, P  = 0.001). Conclusion: Our data suggest that smoking is a risk factor for both PPP development and disease severity. Patients with PPP with PsV present distinct clinical features and patients with biologic therapy‐induced paradoxical PPP have reduced quality of life and are more likely to have PsA.